Campaign Strategies and Social Network Dynamics: Unveiling the Victory of Candidates in the 2024 Legislative Election in Kolaka Regency, Indonesia - Amalia, Dea Rizky; Hidayat, Rahmat; Reski Mulka, Sry; Burhan, Reksa; Mulawarman, M. (Manunggal Halim Jaya, 2025)
This study explores the campaign strategies and the role of social networks in shaping electoral success in the 2024 legislative elections in Kolaka Regency, Indonesia. Using a qualitative approach with a case study design, the research reveals that successful candidates primarily relied on community-based campaign strategies, emphasizing door-to-door outreach, participation in religious and cultural events, and symbolic acts of social solidarity. Rather than formal party platforms, candidates' presence and emotional closeness with voters influenced voter behavior. The findings demonstrate that social networks, particularly kinship ties, religious groups such as Majelis Taklim, and youth communities served as critical channels for political mobilization. Candidates embedded in these networks gained greater visibility and legitimacy, which was essential for electoral trust. In semi-urban areas like Watubangga and Tanggetada, digital platforms such as WhatsApp, Facebook, and Instagram were also used strategically, especially among young voters. However, the effectiveness of digital communication was deeply rooted in offline relational capital. The study also underscores the persistence of patron-client relations in local electoral dynamics. Voter support was frequently driven by past personal assistance, social reciprocity, and community recognition rather than policy considerations. Patronage was not always transactional; it often took the form of moral obligations and long-term social investment. Overall, the research highlights that effective electoral strategies in Kolaka are built on message delivery, sustained social engagement, and embeddedness in local relational structures.